2011
DOI: 10.1007/s00404-011-2156-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum visfatin concentrations in gestational diabetes mellitus and normal pregnancy

Abstract: Plasma visfatin concentrations are lower in patients with GDM and related to glycemic control reflected by HbA1c. Furthermore, visfatin does not seem to be correlated with dietary intake in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
1
19
1
2
Order By: Relevance
“…They used different criteria to diagnose GDM, and no insulin resistance parameters were assessed in their study. Haider et al [16] and Rezvan et al [31] reported similar results at the same gestational age (24-28 weeks). The discrepancy of these findings is unclear but may be related to differences in study design, such as the number of subjects, gestational age at enrollment, or differences in BMI.…”
Section: Discussionsupporting
confidence: 72%
“…They used different criteria to diagnose GDM, and no insulin resistance parameters were assessed in their study. Haider et al [16] and Rezvan et al [31] reported similar results at the same gestational age (24-28 weeks). The discrepancy of these findings is unclear but may be related to differences in study design, such as the number of subjects, gestational age at enrollment, or differences in BMI.…”
Section: Discussionsupporting
confidence: 72%
“…It can therefore be hypothesized that visfatin might act as a positive modulator of glucose homeostasis by delivering the hypothalamic signals into the peripheries. It has also been observed that plasma visfatin concentrations are lower in patients with GDM and related to glycemic control reflected by HbA1c (Rezvan et al, 2012).…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 96%
“…Leptin " in obesity interferes with follicular and oocyte development [68]; counteracts high glucose effect [70]; " in PCOS, BMI-correlated [71] Embryo implantation and embryomaternal cross-talk [72]; # in human implantation failure [73]; " in LGA and # in SGA infants [74] " during normal pregnancy, # around parturition [75]; "" in obese pregnancy [76], delivery disorders [65]; " in GDM, PE [77], # or $ in GDM [78] Adiponectin Positively correlates with the number of oocytes retrieved in ART [79]; # in PCOS [80] BMI-correlated [71] Preimplantation embryo development [81]; promotes trophoblast invasion [82]; placental nutrient transport [83]; inversely correlates with birth weight [84] # during pregnancy in association to the normal pregnancyrelated insulin-sensitivity [85]; # in GDM [86] and PE [88] Resistin Negatively correlates with ovarian response in ART [89]; $ between obese and non-obese PCOS [90] " as pregnancy progresses [57]; "" [91], # or $ in GDM [78] Visfatin In FF correlates with the number of oocytes retrieved in ART [92]; in plasma positively correlate with BMI and PCOS [93]; coadministration with gonadotropins increases fertility [94] " during pregnancy [95]; # [96] and " [97] in GDM; " in PE [98] Omentin # in obesity [99]; expressed in ovary [100]; # in overweight PCOS [101] Detectable in human fetus; no correlation between serum concentration and birth weight …”
Section: Adipocytokinesmentioning
confidence: 99%
“…Increased circulating levels of visfatin and vaspin are associated with T2D; worth of note, concomitant obesity determines a greater increased of both the adipocytokines [200]. Lower [96] and higher visfatin serum levels have been reported in GDM pregnant women compared with controls [97] indicating a certain complexity in the relationship between visfatin, blood glucose, and insulin. A recent study has shown that visfatin serum concentration is increased in women with PE as compared with uncomplicated pregnancy [98].…”
Section: Adipocytokines and Pregnancymentioning
confidence: 99%